2020
DOI: 10.1016/j.tbs.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory investigation of public perceptions towards key benefits and concerns from the future use of flying cars

Abstract: The imminent introduction of flying cars in the traffic fleet is anticipated to modify the mobility patterns of urban commuters. Flying cars' hybrid operation on the ground and in the air, in conjunction with their (semi-) automated capabilities, may lead to more appealing trip considerations, such as travel time, fuel consumption, or environmental emissions, as well as to the emergence of new sources of concerns for the potential users. In this context, the future adoption of flying cars is directly associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…On the contrary, 48.58% and 10.06% respondents indicated that their residences are located at suburban and rural areas, respectively. For additional studies conducted based on the aforementioned survey data, please see Ahmed et al, 2019and Eker et al, (2019a, 2019b. Table 1 presents the responses of individuals' perceptions regarding the safety and security concerns of flying cars as well as regarding potential measures that may enhance the security of flying cars.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, 48.58% and 10.06% respondents indicated that their residences are located at suburban and rural areas, respectively. For additional studies conducted based on the aforementioned survey data, please see Ahmed et al, 2019and Eker et al, (2019a, 2019b. Table 1 presents the responses of individuals' perceptions regarding the safety and security concerns of flying cars as well as regarding potential measures that may enhance the security of flying cars.…”
Section: Datamentioning
confidence: 99%
“…Having semi-or fully-autonomous capabilities for vertical take-off and landing, the operation of flying cars will not significantly differ from conventional personal vehicles during the on-ground operation, and from personal jets during the in-air operation. With provisions for two to four passengers, flying cars are expected to accommodate trips on a distance up to 500 miles, requiring not more than 100 feet (in diameter) clearance zones at the trip origin and destination (see Eker et al, 2019a;Eker et al, 2019b;Ahmed et al, 2019). Recent developments and announcements have shown that flying cars are expected to be introduced in the automotive and aviation market between 2020 and 2025 (Becker, 2017;Oppitz and Tomsu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It was conducted in an online platform called SurveyMonkey, and a total of 692 respondents from 19 different countries participated in the survey. A number of exploratory studies have been conducted so far, based on the data collected in the aforementioned survey (Ahmed et al, 2019;Eker et al, 2019Eker et al, , 2020a. Here, we briefly summarize and illustrate the key issues investigated in the aforementioned works, as they will directly influence future policies and regulations associated with emergent technological advances.…”
Section: Exploratory Human Factors To Inform Future Flying Cars Policymentioning
confidence: 99%
“…The second analysis (Eker et al, 2020a) provides a preliminary investigation in to the public perceptions of forecasted flying car technologies. Specifically, this effort explores the fact that the future adoption of flying cars is directly associated with individuals' perceptions of the benefits and concerns arising from key operational characteristics related to this complex and technologically disruptive technology.…”
Section: Exploratory Human Factors To Inform Future Flying Cars Policymentioning
confidence: 99%
See 1 more Smart Citation